Development and psychometric testing of the actualisation of evidence-based nursing instrument - Parisod, Heidi; Stolt, Minna; Holopainen, Arja; Siltanen, Hannele; Pasanen, Miko; Suhonen, Riitta (John Wiley and Sons Inc, 2025)
Aim: To describe the development of the Actualisation of Evidence-Based Nursing instrument targeted at nurses working in clinical practice (ActEBN-nurses), meant for evaluating the actualisation of individual and organisational-level support structures for evidence-based nursing within social and healthcare organisations, and to test its validity and reliability.
Design: Cross-sectional survey.
Methods: The FinYHKÄ model was used as the theoretical background of the instrument development and supplemented with the JBI Model of Evidence-Based Healthcare, previous literature and items from a previous instrument, the Evidence-Based Practice Process Assessment Scale, with permission of the copyright holders. After two rounds of expert panel and piloting, a national survey was conducted with the instrument in 2021. The target group consisted of nurses working in clinical practice. Psychometric testing included internal consistency (Omega, item analysis) confirmatory factor analysis and t-test for comparison of two groups' differences (sensitivity).
Results: A new instrument, ActEBN-nurses was developed, comprising two parts: Individual-level (32 items, 5-point Likert-scale) and Organisational-level support structures for evidence-based nursing (37 items, 5-point Likert-scale). In total, 1289 nurses participated in the survey. The ActEBN-nurses proved to have good internal consistency in both parts (Omega ω .931 and .966), structural validity and sensitivity based on the two educational levels within the sample. The structure of both parts was slightly modified, based on the CFA modification indices, considering the impact of the reverse worded items in part Individual and redundant items within both parts.
Conclusion: The ActEBN-nurses has promising psychometrics, and it can be used for evaluating individual and organisational-level support structures for evidence-based nursing within social and healthcare organisations.
Implications for the profession and/or patient care: Evaluation of the support structures within social and healthcare organisations is needed to recognise shortcomings in current structures and advance evidence-based nursing across different contexts.
Reporting method: The authors state that they have adhered to relevant EQUATOR guidelines: STROBE statement for cross-sectional studies.
Patient or public contribution: No patient or public contribution.